ZN AND CU ISOTOPIC VARIATIONS IN CHONDRITES AND IRON METEORITES: EARLY SOLAR NEBULA RESERVOIRS AND PARENT-BODY PROCESSES - Luck J.M.; Othman D.B.; Albar?de F. (My University, 2005)
High-precision Zn isotopic variations are reported for carbonaceous chondrites (CC), equilibrated (EOC) and unequilibrated (UOC) ordinary chondrites, iron meteorites from the IAB-IIICD (nonmagmatic) and IIIA (magmatic) groups, and metal from the Brenham pallasite. For irons, δ65Cu values are also reported. Data have also been obtained on a coarse-grained type-B calcium-, aluminum-rich refractory inclusion (CAI) from Allende and on acid leaches of Allende (CV3), Krymka (LL3), and Charsonville (H6). Variations expressed as δ⁶⁶Zn (deviation in parts per thousand of ⁶⁶Zn/⁶⁴Zn in samples relative to a standard) spread over a range of 0.3‰ for carbonaceous chondrites, 2‰ for ordinary chondrites, and 4‰ for irons.